2016
DOI: 10.1111/bju.13493
|View full text |Cite
|
Sign up to set email alerts
|

Chromogranin A and neurone‐specific enolase serum levels as predictors of treatment outcome in patients with metastatic castration‐resistant prostate cancer undergoing abiraterone therapy

Abstract: ObjectiveTo determine the impact of elevated neuroendocrine serum markers on treatment outcome in patients with metastatic castration-resistant prostate cancer (mCRPC) undergoing treatment with abiraterone in a post-chemotherapy setting. Patients and MethodChromogranin A (CGa) and neurone-specific enolase (NSE) were determined in serum drawn before treatment with abiraterone from 45 patients with mCRPC. Outcome measures were overall survival (OS), prostate-specific antigen (PSA) response defined by a PSA level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
68
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(83 citation statements)
references
References 23 publications
14
68
0
1
Order By: Relevance
“…In the literature, a predominance of arbitrary thresholds of neuromediators was chosen after 1-time analysis before therapy to correlate them with outcome. Recently, 2 published trials analyzed CGA before AA therapy and found predictive and prognostic significance [18,19]. Despite the limitations, CGA was shown to be a significant predictive biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, a predominance of arbitrary thresholds of neuromediators was chosen after 1-time analysis before therapy to correlate them with outcome. Recently, 2 published trials analyzed CGA before AA therapy and found predictive and prognostic significance [18,19]. Despite the limitations, CGA was shown to be a significant predictive biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Three hundred and fifty-three papers were identified through joint search keywords and their free-text words from 3 electronic databases and from these papers, 146 articles were excluded by removing of duplicates and 194 were precluded based on titles and abstracts. Finally, 6 of remaining 13 trials met the inclusion criteria and were selected for this meta-analysis [24][25][26][27][28][29].…”
Section: Study Identificationmentioning
confidence: 99%
“…As with the characteristics reflected by Table 1, all included studies were hospital-based retrospective validation studies, of which 3 were cohort studies [24][25][26] and 3 were case-control studies [27][28][29]. All publications were published from 2010 through 2017.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations